Peran Kepuasan Kerja dalam Memediasi Pengaruh Fasilitas Kerja dan Kepemimpinan Melayani terhadap Kinerja Karyawan: Studi pada PT Artha Mandala Pratama - Ramadhani Ikhlas; Eloh Bahiroh; Enis Khaerunnisa (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study aims to examine the role of job satisfaction in mediating the influence of work facilities and servant leadership on employee performance at PT Artha Mandala Pratama. The population of this research consists of all 96 employees of PT Artha Mandala Pratama, who also served as the research sample through a saturated sampling technique. The study employs a quantitative method with a descriptive approach. Data were collected through observation, interviews, questionnaires, and literature studies. The data analysis technique used in this research is Structural Equation Modeling (SEM) with the SmartPLS 4.0 software. The results reveal that work facilities have a positive and significant effect on employee performance. Servant leadership also has a positive and significant effect on employee performance. Furthermore, both work facilities and servant_leadership positively and significantly influence job satisfaction. The findings also indicate that job satisfaction positively and significantly affects employee performance. Moreover, job_satisfaction_partially mediates the relationship between work facilities and employee performance, as well as between servant leadership and employee performance. These results suggest that providing adequate work facilities and implementing servant leadership not only directly improve employee performance but also indirectly enhance it through increased job satisfaction.